The Effects of Saturated and Unsaturated Fat Diets on the Histology of Adrenocortical Cells of Albino Rats A Comparative Study (Medical Forum Monthly, 2024)
Objectives: High fat diet stimulates Hypothalamic -pituitary- adrenal (HPA)axis activity and enhances the release of corticosteroids from adrenal gland which in turn contributes to metabolic syndrome by producing insulin resistance. Present study objectives are to compare the effects of two different types of fat that is saturated and polyunsaturated on the histology of adrenal gland with respect to its activity. Study Design: Prospective experimental. Place and Duration of Study: Department of Anatomy BMSI, JPMC August – October: 2008 Materials and Methods: A total of 30 adult male albino rats weighing 200-240 gm, aged 190 days were divided into three groups. group ‘A’ received standard laboratory diet and group ‘B’ received high saturated fats in the form of unsalted butter as 20% added fat of the total calories. Group ‘C’ received high unsaturated fats in diet i.e. 20% fat added in the form of corn oil of the total calories. Each group was subdivided according to their time of sacrifice i.e. 4 and 8 weeks respectively. Animals were sacrificed at the end of their respective periods by ether anesthesia. Adrenal glands were dissected out, weighed and processed for paraffin embedding and sectioned at 4µm thickness to be stained with H&E, for cell count and cell diameter in the 3 cortical zones. Result: Observations on adrenal gland weight /100gm of body weight of butter and corn oil treated groups revealed moderately significant decrease in weight in corn oil treated group at 4 weeks while there was insignificant difference at 8weeks when compared to butter treated group. There was insignificant difference in cell count in the three zones between butter and corn oil treated groups. Cell diameter in zona fasciculata was significantly increased in butter treated groups at 8weeks when compared to corn oil treated group. Conclusion: Insignificant differences were found in most of the observation between the 2 fat groups. Insignificant difference in adrenal gland weight /100gm body weight between butter and corn oil treated groups at 8 weeks was because of less marked increase in body weight in corn oil treated group. Zona fasciculata showed increase cell size in butter treated group reflecting increased stress hormone release.